Analysis of Weekly Rainfall for Crop Planning in Rainfed Region - Panigrahi, B; Panda, S N (Journal of Agricultural Engineering, 2001)
Probability analysis of rainfall offers a better scope for predicting the minimum assured rainfall to help in crop planning in rainfed regions. In the present study, power transformation is used to normalise the weekly rainfall data and then normal distribution is used to predict the minimum assured rainfall at different probability of exceedance in all weeks of the whole year. In addition, probability of occurrence of different amount of rainfall in various weeks has been estimated. The study reveals that chances of drought are more at critical growth stage of paddy and there is a scope for in-situ moisture conservation and runoff collection in tanks for supplemental irrigation. Rabi crop is found to be grown under moisture stress. Probable values of 1-day maximum rainfall are predicted by power transformation and the values are seen to decrease from 144.7 to 48.1 mm as probability of exceedance increases from 5 to 95%.